Understanding ecological transitions under recurrent wildfire: a case study in the seasonally dry tropical forests of the Chiquitania, Bolivia - Devisscher, T; Malhi, Y; Landivar, V; Oliveras, I (Elsevier, 2015)
Wildfires in tropical forests are likely to become a more dominant disturbance due to future increasing feedbacks between rapid frontier expansion and more frequent droughts. This study evaluates the effects of fire recurrence on seasonally dry tropical forests of the Chiquitania region, located in the southern rim of Amazonia, eastern lowlands of Bolivia. Effects were assessed in terms of changes in biomass, forest structure, species diversity and composition. Forest plots were established in well-conserved study sites to compare unburnt forests with forests burned once, twice and three times in the period 2000-2012. Inventories were collected for trees, palms and lianas, including identification of species and measurement of morphological traits related to fire tolerance. Biomass was estimated using different allometric equations, and species composition, richness, abundance and dominance were compared. We found a significant loss in biomass, and putative effects on small and large trees after recurrent burns. The observed patterns in this study suggest that Chiquitano forests respond to recurrent fires through a shift in tree species composition with already-present fire-tolerant species becoming more dominant. This transition presented losses in biomass but increases in species richness. Insights into a possible transition to a more fire-adapted state is of great relevance for forest and fire management strategies in the region, as this transition may become irreversible in a future regime of more frequent wildfires, expected due to drier climatic conditions with increasing patterns of forest fragmentation and spreading use of fire into new forest frontiers.